(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Cloud-based disaster recovery (DR) solutions help organisations recover from natural disasters and cyberattacks quickly and affordably. Cloud-based disaster recovery solutions improve recovery times, capital costs, scalability, and security. Yet, data security and DR strategy are still barriers to adoption. Only two issues. Besides these challenges, cloud-based catastrophe recovery looks promising. Cloud-based disaster recovery solutions will continue to grow as cloud technology improves. Hybrid cloud disaster recovery solutions, which integrate public and private cloud environments, will continue to grow in popularity, as will DRaaS, a cost-effective and flexible disaster recovery solution. As cloud-based disaster recovery solutions grow more prevalent, organisations must understand their disaster recovery needs, carefully analyse their cloud service providers’ security and compliance procedures, and regularly test and update their disaster recovery plans and solutions. If organisations follow these measures, they may maximise the benefits of cloud-based disaster recovery solutions to safeguard their critical data and apps and ensure business continuity in a disaster.